Assessing effects of EU regulation on cryptocurrency trading: an analysis on bitcoin - Thieme, Sarah Marie (2022)
The increasing popularity and presence of cryptocurrencies challenge regulators in providing adequate policy tools to handle the borderless, decentralized virtual assets. This paper examines the impact of EU regulatory announcements on Bitcoin trading through an event study on a unique data set. A bnormaltrading volumes of Bitcoin following key regulatory announcement are analyzed and show statistically significant impact on trading activity. The impact depends on the crypto-fiat currency pair and is observed to decrease BTC/EUR trading, while the opposite is detectable for BTC/USD. These results suggest that crypto currencies rely on centralized, regulated financial intermediaries, which bring them within reach of regulation